A comparative analysis of osteocranium morphology in Lutjanus johnii (Bloch, 1792) and Lutjanus gibbus (Forsskal, 1775) inhabiting different habitats - Muhammad Radhi; Firdus Firdus; Zainal Abidin Muchlisin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
The snapper species Lutjanus gibbus (L. gibbus) is commonly found in coastal areas characterized by coral reefs and clear water, while Lutjanus johnii (L. johnii) resides in mangrove waters with murky conditions and strong currents. The habitat plays a crucial role in influencing body shape and ossification patterns in fish. Therefore, this study aimed to examine the differences in the cranial bone morphology between the two Lutjanus fish species that resided in contrasting habitats. The fish samples were collected from local fishermen operating in the waters of Pulo Aceh, Aceh Besar, Indonesia. Following capture, the fish were transported and landed at Lampulo Fishing Port in Banda Aceh for further analysis. For each species, a total of 5 fish samples were randomly selected, and thorough cleaning of scales and muscles was performed before the drying of the bones. These dried cranial bones were then photographed, edited, and subjected to detailed analysis. The study showed that, of the 23 observed skull bone characters, 15 characters showed the differences in the cranial bones of the two snapper species, including the pre-ethmoidal, ethmoidal lateralis, prefrontal, supraorbital, nasal, ethmoidal, sphenoticum, crista occipital, lacrimal, inter-opercular, opercular, preopercular premaxilla, endopterygoideum, and hyomandibular. Significant differences were observed in the bones composing the eyes, nose, jaws, and ventral region of the head. In the mangrove snapper (L. johnii), the bones associated with the eyes (orbitospenoidal, supraorbital, and prefrontal) were less developed, while those related to the nose (nasal, ethmoidal, ethmoidal lateralis, pre-ethmoidal) showed well-developed characteristics. The coral snapper L. gibbus displayed a relatively small but thicker premaxilla bone in the jaw region, along with smaller bones in the ventral head area.Keywords:OsteologyMorphologyEcomorphologyOsteocraniumMaxillare